Frequency and impact on renal transplant outcomes of urinary tract infections due to extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella species - Brune, Jakob E.; Dickenmann, Michael; Sidler, Daniel; Walti, Laura N.; Golshayan, Déla; Manuel, Oriol; Haidar, Fadi; Neofytos, Dionysios; Schnyder, Aurelia; Boggian, Katia; Mueller, Thomas F.; Schachtner, Thomas; et al. (Frontiers in Medicine, 2024)
Background Enterobacterales are often responsible for urinary tract infection (UTI) in kidney transplant recipients. Among these, Escherichia coli or Klebsiella species producing extended-spectrum beta-lactamase (ESBL) are emerging. However, there are only scarce data on frequency and impact of ESBL-UTI on transplant outcomes. Methods We investigated frequency and impact of first-year UTI events with ESBL Escherichia coli and/or Klebsiella species in a prospective multicenter cohort consisting of 1,482 kidney transplants performed between 2012 and 2017, focusing only on 389 kidney transplants having at least one UTI with Escherichia coli and/or Klebsiella species. The cohort had a median follow-up of four years. Results In total, 139/825 (17%) first-year UTI events in 69/389 (18%) transplant recipients were caused by ESBL-producing strains. Both UTI phenotypes and proportion among all UTI events over time were not different compared with UTI caused by non-ESBL-producing strains. However, hospitalizations in UTI with ESBL-producing strains were more often observed (39% versus 26%, p = 0.04). Transplant recipients with first-year UTI events with an ESBL-producing strain had more frequently recurrent UTI (33% versus 18%, p = 0.02) but there was no significant difference in one-year kidney function as well as longer-term graft and patient survival between patients with and without ESBL-UTI. Conclusion First-year UTI events with ESBL-producing Escherichia coli and/or Klebsiella species are associated with a higher need for hospitalization but do neither impact allograft function nor allograft and patient survival.